In silico characterisation of the Glaciozyma antarctica Genome: mining the molecular chaperones - Nur Athirah, Y.; Abu Bakar, F.D.; Illias, R.M.; Mahadi, N.M.; Murad, A.M.A. (Penerbit Universiti Kebangsaan Malaysia, 2015)
Glaciozyma antarctica is a psychrophilic yeast isolated from the Antarctic sea ice. In this study, we performed a de novo characterisation of molecular chaperones from G. antarctica genome datasets. A total of 7857 genes that code for various types of proteins have been predicted from the G. antarctica genome sequence. From these genes, we identified 89 possible molecular chaperones that matched known molecular chaperones from other organisms available in various databases such as Uniprot, Gene Ontology, cpnDB and NCBI. For an in-depth analysis of molecular functions, we used homologous clustering to transfer knowledge from unknown to known functions using Cluster Analysis of Sequences (CLANS) bioinformatics software. The results reveal 12 major groups of chaperones that contribute to the cold-adaptation mechanism through their molecular function, biological processes and cellular components. The findings lay the foundation for future functional genomics studies on this organism and shed light on how lower eukaryotic cells respond to low temperature.